(untitled) (Rupandehi Campus Journal, 2022)
Thyroid gland is vital gland. It produces Thyroxine T3 and Tri-Idothyronine T4 hormones which are needed for the growth and development. Iodine is needed for the formation of T3 and T4 hormones. Iodine is found in different food such as sea food, vegetables produced in Iodine rich soil and table salt. The associated problems of thyroid gland are hypothyroidism and hyperthyroidism. The objective of this study was to find out the prevalence of thyroid problems attending at Siddharthanagar City Hospital. It was hospital based retrospective study. Data related to thyroid problems T3,T4 and TSH was collected from hospital laboratory reports . The tests were done using Semi Auto Clia Plate Analyzer of TOSOH India Company. The total number of lab reports was 299 taken for study. Among them the percentage of male and female was 21.7 and 78.3 respectively. The overall prevalence of thyroid problems was 5.9% among general public. The overall prevalence of hypothyroidism was 9.69% and hyperthyroidism was 2.17% respectively. The prevalence of thyroid problems was seen more in female. This study showed that thyroid problem including hyperthyroidism and hypothyroidism is common. Female population and 21-40 years age group are highly suffered in comparison to male population.